2004
DOI: 10.1167/iovs.04-0686
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Kinase CK2 in Angiogenesis and Retinal Neovascularization

Abstract: This is the first demonstration of the involvement of ubiquitous protein kinase CK2 in angiogenesis. Naturally derived CK2 inhibitors may be useful for treatment of proliferative retinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 71 publications
3
66
0
Order By: Relevance
“…Two CK2 inhibitors, namely emodin and tetrabromobenzotriazole (TBB), were found to significantly reduce retinal neovascularization [66]. Later on, it was tested whether the effect of CK2 inhibitors would be enhanced if they were contributed with other anti-angiogenic drugs with a different mode of action.…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…Two CK2 inhibitors, namely emodin and tetrabromobenzotriazole (TBB), were found to significantly reduce retinal neovascularization [66]. Later on, it was tested whether the effect of CK2 inhibitors would be enhanced if they were contributed with other anti-angiogenic drugs with a different mode of action.…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…Early reports describing the use of CK2 inhibitors in vivo in mouse models, in which no evident toxicity has been observed, supported this notion. 55,56 Most importantly, very recently a phase-I clinical trial started in USA, sponsored by Cylene Pharmaceuticals, which is testing safety, tolerability and highest dose level of the CK2 inhibitor CX-4945 in patients with advanced solid cancers, Castleman's disease or MM (NCT00891280). Preliminary results have displayed very encouraging results, 46 and later a myeloma-dedicated phase-I trial has started (NCT01199718).…”
Section: The Therapeutic Potential Of Ck2 Inhibition In Blood Tumorsmentioning
confidence: 99%
“…CK2 is markedly augmented in a wide range of cancers (18) and appears to enhance malignant transformation by creating a more hospitable environment for tumor growth (19). CK2 also stimulates angiogenesis (20) as well as multidrug resistance (21). Pandolfi and coworkers demonstrated that the tumor suppressor promyelocytic leukemia protein (PML) is a physiologic substrate of CK2 (22).…”
mentioning
confidence: 99%